Characterization of the innovation management in manufacturing sector enterprises of Boyacá (2011)
The contemporary company faces new challenges, hence innovation takes a leading role in the success of the company against its competitors, providing different features that are as competitive advantages. In this article we present the results of the research on the impact of science, technology and innovation policies, in building capacity in management of innovation in the manufacturing sector of the department of Boyacá.